2010
DOI: 10.1017/s1041610210001912
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation for dementia using enjoyable video-sports games

Abstract: The aging of society inevitably leads to an increase in the numbers of elderly with dementia who reside in nursing homes, and delaying disease progression of residents with dementia has become a big concern. Rehabilitation that focuses directly on training cognitive function (e.g. memory training) reveals what patients are unable to do. Realization of their cognitive deficits can devastate their self-confidence and lead to anxiety, depression and the lowering of self-esteem (Small et al., 1997). We propose reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 5 publications
2
63
0
Order By: Relevance
“…In the latter papers, it was implied that the perceived, by the elderly users, usefulness of the physical exercise through exergames contributes to their motivation and their subsequent adherence to the exercise protocol. In accordance with other studies, it was also reported that exergames can positively impact many health areas, such as balance, gait [9], motion control [10], quality of life [5], mood and sociability [11, 12], self-esteem and reduced risk for depression [13]. Regular exercise at home could help to prevent diseases aggravated by a sedentary life imposed by conditions such as cardiovascular diseases and stroke [14].…”
Section: Introductionsupporting
confidence: 60%
“…In the latter papers, it was implied that the perceived, by the elderly users, usefulness of the physical exercise through exergames contributes to their motivation and their subsequent adherence to the exercise protocol. In accordance with other studies, it was also reported that exergames can positively impact many health areas, such as balance, gait [9], motion control [10], quality of life [5], mood and sociability [11, 12], self-esteem and reduced risk for depression [13]. Regular exercise at home could help to prevent diseases aggravated by a sedentary life imposed by conditions such as cardiovascular diseases and stroke [14].…”
Section: Introductionsupporting
confidence: 60%
“…In the field of training, most of the research work so far has been conducted employing commercial video-games and cognitive games (such as Wii Fit and Wii Sport, Lumosity) designed for an entertaining purpose, and with a ‘typical’ healthy user in mind. In their review on the use of video-games in people with dementia-related disorders, McCallum and Boletsis (2013) showed that: (a) Exergames, i.e., games that promote physical condition and/or aerobic fitness can positively affect several areas of mobility in participants with mild AD and MCI, such as balance and gait (Padala et al, 2012), and voluntary motor control (Legouverneur et al, 2011); (b) cognitive games can improve cognitive functions, such as attention and memory (Stavros et al, 2010; Weybright et al, 2010) and visuo-spatial abilities (Yamaguchi et al, 2011); (c) physical and cognitive games can have a positive impact on social and emotional functions, for instance they can improve the mood and increase positive affect and sociability (Weybright et al, 2010; Boulay et al, 2011) and reduce depression (Férnandez-Calvo et al, 2011). As the field is young, less evidence is available on the efficacy of SG specifically designed for the training of people with ND.…”
Section: Introductionmentioning
confidence: 99%
“…McCallum and Boletsis (2013) performed a literature review of the experimental studies conducted to date on the use of SG in neurodegenerative disorders. In summary, the results of the 15 reported studies suggest that: (1) physical games (or exergames, i.e., games that promote physical fitness) can positively affect several health areas of the players with mild AD and MCI, such as balance and gait (Padala et al, 2012), and voluntary motor control (Legouverneur et al, 2011); (2) cognitive games (i.e., games which target cognitive improvement) can improve a number of cognitive functions, such as attention and memory (Stavros et al, 2010; Weybright et al, 2010; Rosen et al, 2011) and visuo-spatial abilities (Yamaguchi et al, 2011); (3) both physical and cognitive games can have a positive impact on social and emotional functions, for instance they can improve the mood and increase positive affect and sociability (Weybright et al, 2010; Boulay et al, 2011; Yamaguchi et al, 2011) and reduce depression (Férnandez-Calvo et al, 2011). Very few studies investigated the effects of the use of games for social/emotional health (which encourage the players to link with their friends and/or improve their social and emotional life) in dementia, but the results are encouraging (Boulay et al, 2011).…”
Section: Introductionmentioning
confidence: 99%